Weak convergence for equilibrium problems involving nonexpansive and nonspreading multivalued mappings: Watcharaporn Cholamjiak, Prasit Cholamjiak - Team, Support (Thai Journal of Mathematics, 2020)
In this paper, we introduce iterative methods to approximate a common element ofthe sets of fixed points of a nonexpansive multivalued mapping and a12-nonspreading multivalued mapping and the set ofsolutions of equilibrium problems and prove some weakconvergence theorems of the sequences generated by our iterativeprocess under appropriate additional assumptions in Hilbert spaces.As applications, we give the example and numerical results. Theresults obtained in this paper extend and improve some recentresults.